Preserving Neural Retina Through Re‐Emerging Herbal Interventions. Issue 10 (October 2014) - Anand, Akshay; Modgil, Shweta; Sharma, Vijay Lakshmi; Shri, Richa; Kaushik, Sushmita
Abstract Eye related diseases such as glaucoma, diabetic retinopathy, cataract, conjunctivitis are very common worldwide. With the current scenario India will be among the top five countries in the number of glaucoma cases. Limited discovery of successful drugs for the treatment of such diseases led scientists to look towards the use of conventional sources for treatment. Herbal extracts from Ayurveda have remained an important part of treatment regime in many parts of world even today. For this reason, local herbs possessing curative properties are still being used by local inhabitants due to its anti‐inflammatory and antioxidant properties. Because retinal damage involves alterations in oxidative enzymes, blood flow changes and increase in apoptotic signals, herbal extracts are being tested for their ability to moderate antioxidant machinery and trigger neuroprotective pathways. The present review summarizes some of such herbal extracts which have been tested for their neuroprotective role in eye related diseases. The active components that exert neuroprotective effects have also been discussed along with possible mechanisms of action. J. Cell. Biochem. 115: 1659–1668, 2014. © 2014 Wiley Periodicals, Inc.